Leveraging Digital Health Data to Transform the United Nations Systems for Palestine Refugees for the Post Pandemic Time - Akihiro Seita; Ghada Ballout; Shatha Albeik; Zaid Salameh; Wafaa Zeidan; Sayed Shah; Saed Atallah; Masako Horino (Taylor & Francis Group, 2024)
The COVID-19 pandemic presented a grave threat to the continuity of health services that UNRWA provides to 5.9 million Palestine Refugees in the Near East. UNRWA runs 140 primary health care clinics, providing approximately nine million medical consultations a year. During the pandemic, UNRWA's e-Health system (and other digital health tools) were crucial in maintaining health services. The e-Health system enabled the identification of at-risk patients and transformed UNRWA's services for sustainability and efficiency. Innovations like telemedicine and two smartphone applications (e-NCD and e-MCH) enhanced service delivery and staff management. To evaluate the effectiveness of digital health integration in UNRWA's services during and after the pandemic, the team analyzed reports, events, and e-Health data from 2019-2022. Results show that digital tools, like e-NCD and e-MCH applications, helped reduce COVID-19 among Palestine Refugees, enabling remote care and continuous access to essential health services. Digital health has now become essential in UNRWA's post-pandemic operations. This paper offers a paradigm for future outbreak responses. By harnessing the power of digital health, UNRWA's e-Health system served as a beacon of hope, demonstrating how innovative approaches can empower patients, enhance health care outcomes, and ensure equitable access to health care services during crisis situations and beyond.